2012
DOI: 10.1352/1944-7558-117.6.455
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Prevalence of Chronic Disease Among People with and Without Intellectual Disability

Abstract: Some studies have reported the presence of health disparities in people with intellectual disability. This study compared the prevalence of chronic health conditions between people with and without intellectual disability (ID). Health-related data for 791 people with ID were collected through a province-wide mail survey in Quebec, Canada. The distribution of chronic health conditions reported was compared to the data on the health status of the general population. People with ID had higher reported rates of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 18 publications
2
66
1
Order By: Relevance
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Primarily, the included studies were cross-sectional observational (n = 31 81,82,98,[100][101][102]104,106,[109][110][111]114,116,119,121,124,[126][127][128][129][130][131][132][133][134][135]137,139,142,143,145 ). The remaining studies involved retrospective database or medical records data (n = 22 [83][84][85][86][87][88][89]94,95,99,107,113,115,117,118,120,122,123,136,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…People with intellectual disability receive less health promotion and screening than do members of the general population, despite their arguably greater need across multiple domains. [9][10][11] People with intellectual disability have the right to the highest attainable standard of health. 12 researchers have a critical role to contribute to reductions in health inequities experienced by this group by generating an appropriate evidence base Abstract Aims: Adults with intellectual disability experience substantial health inequities.…”
Section: Peer Reviewmentioning
confidence: 99%
“…It has been shown that people with ID in the community often have multiple coexisting physical health needs, such as respiratory disease, cardiovascular disease, neurological conditions, weight problems, diabetes, foetal alcohol spectrum disorder and sensory losses such as hearing and vision impairments (Morin et al . ; Slevin et al . ; Turk et al .…”
Section: Introductionmentioning
confidence: 99%